Evaluation of elephant grass Taiwan A-148 cultivar for ensilage - Tosi, Hugo; Faria, Vidal Pedroso de; Gutierrez, Luiz Eduardo; Silveira, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
A study on the ensilage potential of elephant grass (Pennisetum purpureum Schum.), Taiwan A-148 cultivar. Through 200 kg/ha of the formula 4-34-11 and top dressing with 500 kg/ha of ammonium fertilization and early cut, a high nutritive value forage with 10.61%crude protein was obtained. A 3 x 2 factorial arrangement was used to study three moisture levels (natural, 8 hours, and 12:30 hours of wilting) under solar radiation versus two forage treatments (with and without 4% of molasses). Elephant grass presented excessive moisture, thus justifying previous wilting, which made possible an average of 15.50 to 24.70% of dry matter. Molasses addition was responsible for significant increases of soluble carbohydrate and glucose in this cultivar. So it was proposed that it would not be necessary to include molasses for stimulating lactic fermentation. Buffering capacity to hydrochloric acid was also high due to the young growth stage of forage.